Pergerakan Pesawat Komersial Terhadap Pergerakan Penumpang di Bandara - Hanif Bambang; Dwinda Rachmawati; Haris Simak (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The purpose of the research is to find out the effect of aircraft flying frequency to passengers’ movement in Halim Perdanakusuma International Airport from 2016 to 2017. The problem of the research is how the flying frequency of commercial aircraft in Halim Perdanakusuma International Airport effects the passengers’ movement in 2016-2017. The analysis techniques used in this study were simple linier regression, coefficient correlation, determinant coefficient and hypothesis test. The first result is Y = 140152 + 75,96X (from simple linier regression analysis) which means each changes from one variable X will be followed by Y changes of 75.96 times X in constant of 140152. The second result is 0.74 from coefficient correlation analysis which shows there is a strong and positive relation between commercial aircrafts’ flying frequency and passengers’ movement. The third result 55 % is from determinant coefficient analysis which shows the contribution of variable X (aircraft flying frequency) to variable Y (passengers’ movement) while the other 45 % is from other factors. The last result is 5.18 and 1,717 or > (5.18 > 1,717) from hypothesis test which means there is a significant relation between X and Y variables (Ho is rejected while Ha is accepted).